Innovation characteristics and technology adoption on Probio_FM in the implementation of an integrated farming system in Bangka Tengah - Rufti Puji Astuti; Novyandra Ilham Bahtera; Fournita Agustina (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The strategy to disseminate innovative technology is vital. It expects the technology to be effective and can be adopted. The assessment of the perception of farmers towards the characteristics of innovative technology is needed to identify the potential implementation of sustainability. The study aims to understand the characteristics of technology innovation of Probio_FM in the food processing of palm oil and to examine the impact of innovation characteristics on the adoption of innovation. The survey was employed as the research method. Structural equation modeling with smart partial least squares was used to analyze the data. The study discovered that the innovation characteristics and adoption of Probio_FM technology were relative advantages, compatibility, complexity, liability, and observability. The innovation characteristics had a significant impact on the adoption process. Technology innovation was accepted by society. The variable of relative advantage, trialability, and compatibility was the most important innovation characteristic of livestock farmers in the process of adoption of Probio_FM technology in food processing of palm oil.